PNG Health Workforce Crisis : A Call to Action - World Bank (Washington, DC, 2017)
This report documents for the first time in over a decade the current stock of the publicly financed health workforce in PNG and their characteristics and deployment across the country by type of health facility and health cadre. It also documents the capacity of the health-related training institutions and presents the results of an important survey of health training institutions which enable unit costs, staffing and other aspects of the institutions to be analyzed together with a qualitative assessment of the quality of students and of facilities by training school principals. The report presents a set of five demand scenarios and draws out the implications for the health training system and of the health budget for these scenarios. The National Health Plan 2011-2020 (NHP) recognizes that the emerging crisis in the health human resources area is a critical issue confronting any viable strategy designed to implement the objectives it has set for the health sector. This report helps document the nature of this emerging crisis and makes specific recommendations on the way forward.